Deskripsi Faktor Individu dan Faktor Pekerjaan terhadap Kelelahan Kerjan pada Operator Container Crane (CC) di Terminal Petikemas Nilam - Muhammad Ilham Rizqi Dermawan; Muslikha Nourma Rhomadhoni; Friska Ayu; Merry Sunaryo (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
Nilam Container Terminal is one of the operational areas of PT Pelindo Container Terminal. The Terminal is divided into two areas which include Multipurpose patchouli and conventional patchouli. One of Nilam Container Terminal Services is container loading and unloading services. One of the container loading and unloading activities is assisted by a container crane. Nilam Container Terminal has 4 container cranes weighing 40 tons. Container crane operators must focus and concentrate while working so that the mental workload received is high, it certainly has an impact on work fatigue. Age is also an individual factor causing work fatigue. In addition, the period of work is also a cause of work fatigue in the work factor. The purpose of this study was to determine the description of individual factors and occupational factors to work fatigue in container crane operators in Nilam Container Terminal. This research is descriptive analytic research using cross sectional approach method. Sample research used as many as 24 people who are operators of Container crane Container Terminal Nilam. Data were collected using individual characteristics questionnaires, NASA-TLX and IFRC. The results of data analysis on the description of individual factors of work fatigue obtained by workers who experience work fatigue are mostly workers with late adulthood (26-35 years) and early elderly (46-55 years). in the work factor, it was found that workers who experienced work fatigue mostly had a working period (6-10 years) and (>10 years). Keywords: Work fatigue, Container Crane Operator, IFRC